Response of blood biomarkers to sprint interval swimming - Kabasakalis, A.; Nikolaidis, S.; Tsalis, G.; Mougios, V. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To evaluate and compare the effects of 2 sprint interval training (SIT) sets of different distances on biochemical markers indicative of metabolism, stress, and antioxidant capacity in competitive swimmers and, to investigate the potential influence of gender on these markers. Methods: Twenty-four adolescent, well-trained swimmers (12 men and 12 women) participated in the study. In a random and counterbalanced order, the swimmers completed 2 SIT sets (8 × 50 m and 8 × 25 m) in freestyle with maximal intensity on different days. Work-to-rest ratio was 1:1 in both sets. Blood samples were drawn preexercise, immediately postexercise, and 1 hour postexercise to evaluate the effects of the SIT sets on a number of biochemical parameters. Results: Swimming speed was higher at 8 × 25 m. The 2 SIT sets induced significant increases in lactate, glucose, insulin, glucagon, cortisol, and uric acid (P = .001). No differences in these parameters were found between sets, except for irisin (higher in 8 × 50 m; P = .02). Male swimmers were faster and had higher lactate and uric acid concentrations, as well as lower reduced glutathione concentration, than female swimmers (P < .01). Conclusions: The 2 swimming SIT sets induced increases in most of the biochemical markers studied. The 2-fold difference between sets in distance did not differentiate the effects of sprint interval exercise on most biochemical parameters. Thus, low-volume SIT sets seem to be effective stimuli for competitive swimmers.